HPLC analysis, acute toxicity and anti-inflammatory effects of Salix alba L. barks extracts on experimental animal models (Indian Journal of Experimental Biology (IJEB), 2022)
The white willow, Salix alba L., rich in polyphenols and flavonoids, is traditionally used for its antipyretic, analgesic and anti-inflammatory potential in Algeria. As part of the ethnobotanical survey of medicinal plants in Setif region in Algeria, in the present study, we assessed the safety profile of S. alba barks methanol (SAME) and aqueous (SAQE) extracts, their phytoconstituents, and their antioxidant and anti-inflammatory activities. The in vitro antioxidant activity was evaluated by 2, 2-diphenyl-1-picrylhydrazyl radical (DPPH), reducing power and hydroxyl radical tests assays. HPLC analysis identified 16 compounds in each extract with different concentrations. Gallic acid, syringic acid and cinnamic acid were high in the aqueous extract, while the methanol extracts were rich in chlorogeni cacid, catechin, methyl gallate, pyrocatechol, rutin, ferulic acid, naringenin, taxifolin and kaempferol. The extracts showed significant reducing power, DPPH and hydroxyl radical scavenging effects. In vivo tests showed a strong effect on carrageenan-induced paw edema after 5 h with an inhibition of 88.62 and 87.56% for SAME and SAQE (500 mg/kg), respectively. The extracts also at 500 mg/kg showed significant inhibition of xylene-induced ear edema of 57.81% with SAME 67.18% with SAQE. The results have shown that the methanol and aqueous extracts of the barks of S. alba had no toxic effect on biochemical parameters as well as the organ weights and behaviour. It indicates that S. alba could be a promising source of anti-inflammatory agent.